ONLINE TEACHING OF MEDICAL STUDENTS DURING COVID -19 PANDEMIC – TEACHERS’ PERSPECTIVE: A CROSS-SECTIONAL STUDY. - Mehandiratta, Rachna; Takkar, Vikrom (Student's Journal of Health Research Africa, 2024)
Background The COVID-19 pandemic forced educational institutions to transition from traditional in-person teaching to online learning environments. In medical education, this shift posed unique challenges due to the reliance on hands-on and clinical teaching methods. The rapid switch to digital platforms was essential to ensure the continuity of medical education, despite the limitations and lack of preparedness. This study assessed the faculty's perceptions of online teaching during the COVID-19 lockdown. Methodology A cross-sectional observational study was conducted among the teaching faculty of Dr. Y. S. Parmar Government Medical College (DYSPGMC), Nahan. Feedback was collected via online Google Forms from April 2020 to September 2020. A total of 50 faculty members were invited to participate, and 29 responses were received. The survey utilized a Likert scale to evaluate comfort with online teaching tools, feedback on effectiveness, interaction with students, syllabus completion, and content delivery. Results 75.9% of the faculty preferred PowerPoint presentations, with 37.9% incorporating narrative audio. Additionally, 44.8% used online videos, and 27.6% shared PDF notes. 44.8% of the teachers rated student interaction during live lectures as moderately good, while 37.9% found it very good. Only 27.6% of the faculty reported that lectures were completed within the stipulated time. 44.8% of respondents found the online teaching tools convenient, but 10.3% reported poor audio-visual quality due to network issues. Conclusion The study concluded that online classes were generally accepted by the faculty, but challenges such as limited student interaction and technological difficulties were prevalent. Although online teaching helped maintain the continuity of education during the pandemic, faculty members expressed that it cannot fully replace traditional classroom and clinical instruction. Recommendation To improve the online teaching experience, institutions should provide better IT support, including high-speed internet, premium access to online teaching platforms, and dedicated teaching spaces.